2009
DOI: 10.1016/j.expneurol.2009.07.018
|View full text |Cite
|
Sign up to set email alerts
|

The complement cascade as a therapeutic target in intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is the second most common and deadliest form of stroke. Currently, no pharmacologic treatment strategies exist for this devastating disease. Following the initial mechanical injury suffered at hemorrhage onset, secondary brain injury proceeds through both direct cellular injury and inflammatory cascades, which trigger infiltration of granulocytes and monocytes, activation of microglia, and disruption of the blood–brain barrier with resulting cerebral edema. The complement cascade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 66 publications
1
93
0
Order By: Relevance
“…Very few studies have evaluated adipokines in relation to ICH although C3 has been implicated in ICH pathogenesis [23,13,10]. We did see differences in the %ASP/C3, ASP, and C3 but not adiponectin, as has been shown with ICH and stroke in a previous study [24].…”
Section: Discussionsupporting
confidence: 61%
“…Very few studies have evaluated adipokines in relation to ICH although C3 has been implicated in ICH pathogenesis [23,13,10]. We did see differences in the %ASP/C3, ASP, and C3 but not adiponectin, as has been shown with ICH and stroke in a previous study [24].…”
Section: Discussionsupporting
confidence: 61%
“…Edema formation that occurs in the peri-hematomal region is likely because of increased BBB damage, which contributes to consequent neuronal loss and delayed brain injury after ICH. 33,34 We found that after 3 days of ICH, mice treated with rADAMTS 13 developed significantly less brain edema and smaller hemorrhagic lesion volume as compared with the control group. These data suggest that the protective effect of rADAMTS 13 on hemorrhagic brain injury is most likely caused by the reduction in inflammation-related BBB dysfunction.…”
Section: Strokementioning
confidence: 79%
“…Apart from activating microglia and complement C3, 23 CRP can directly cause blood-brain barrier disruption and brain edema formation. 24 Experimental studies demonstrate that an acute local inflammatory response to the hematoma can occur within 1 hour of onset, 25 and a systemic state of inflammation is triggered.…”
Section: Prediction Of Ehg and Enwmentioning
confidence: 99%